(untitled) (Nóema, 2013)
The essay analyses the notion of the subject in Kant, starting from the lyotardian reading of the Analytic of Sublime. The dismantling of the architectural critics, carried out by the French philosopher in the name of the sentimental a priori, which opposes to a priori of the categorical logic, will cause a review of the ontological value of the “I think”, implying its capitulation as a basis.